Mass Casualty Incident Involving Rapid Acting Insulin. (3rd April 2023) - Liao, Mark Y.; Fulks, Tyler; Garner, Jason; Supples, Michael; Glober, Nancy King
Abstract: We report on an unusual prehospital incident involving the inadvertent administration of short-acting insulin among a group of high school students. Sixteen students iatrogenically received 10 units of insulin lispro intradermally instead of tuberculin purified protein derivative (PPD), resulting in several students experiencing symptomatic hypoglycemia. A mass casualty incident was declared and the local poison center consulted. An incident command system, with the support of on-scene EMS physicians, was established to track, treat, and transport the involved patients.